Testing a counselling intervention in antenatal care for women experiencing partner violence: a study protocol for a randomized controlled trial in Johannesburg, South Africa - Christina Pallitto; Claudia García-Moreno; Heidi Stöeckl; Abigail Hatcher; Catherine MacPhail; Keneoue Mokoatle; Nataly Woollett (BMC, 2016)
Abstract Background Intimate partner violence (IPV) during or before pregnancy is associated with many adverse health outcomes. Pregnancy-related complications or poor infant health outcomes can arise from direct trauma as well as physiological effects of stress, both of which impact maternal health and fetal growth and development. Antenatal care can be a key entry point within the health system for many women, particularly in low-resource settings. Interventions to identify violence during pregnancy and offer women support and counselling may reduce the occurrence of violence and mitigate its consequences. Methods Following a formative research phase, a randomized controlled trial will be conducted to test a nurse-led empowerment counselling intervention, originally developed for high-income settings and adapted for urban South Africa. The primary outcome is reduction of partner violence, and secondary outcomes include improvement in women's mental health, safety and self-efficacy. The study aims to recruit 504 pregnant women from three antenatal clinics in Johannesburg who will be randomized to the nurse-led empowerment arm (two 30-min counselling sessions) or enhanced control condition (a referral list) to determine whether participants in the intervention arm have better outcomes as compared to the those in the control arm. Discussion This research will provide much needed evidence on whether a short counselling intervention delivered by nurses is efficacious and feasible in low resource settings that have high prevalence of IPV and HIV. Trial registration The study was registered in the South African Clinical Trials Registry (DOH-27-0414-4720) on 11 August 2014 and in the ISRCTN Registry ( ISRCTN35969343 ) on 23 May 2016).